2021
DOI: 10.1177/16094069211038400
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Research as a Complex System

Abstract: Collaborative research has become increasingly prominent since the mid-20th century. This article aspires to offer a fundamental ontology of a multidisciplinary research system. As a point of departure, we consider disciplinarity as a restricted language code as noted by Bernstein. The impetus for collaboration is found in a research problem’s transcendence of disciplinary bounds. This article makes several propositions that diverge from the consensus position regarding the formation and dynamics of a multidis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…We developed the second research question iteratively as thematic categories emerged during the data analysis process (detailed later). This methodological iterative approach to study design and analysis allowed us to incorporate what we were learning as the research went on, rather than following a set of rigid linear steps that can dampen the richness of the data set 18. By iterating this second research question as the study progressed, we were able to more accurately reflect what the data revealed, rather than what we, as researchers, may have been looking for.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We developed the second research question iteratively as thematic categories emerged during the data analysis process (detailed later). This methodological iterative approach to study design and analysis allowed us to incorporate what we were learning as the research went on, rather than following a set of rigid linear steps that can dampen the richness of the data set 18. By iterating this second research question as the study progressed, we were able to more accurately reflect what the data revealed, rather than what we, as researchers, may have been looking for.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We suggest that the central organizing principle, by virtue of a stricter definition of the metaproblem, seeks to impose the dynamics of a complicated system, notably in terms of increased centralized control, onto what is in fact intrinsically a complex system. With the establishment of a form of centralized control, a system becomes more mechanistic and formalized – as is characteristic of a complicated system - especially compared to the dynamism of a multidisciplinary system as discussed in Dalton et al (2021).…”
Section: Interdisciplinary Research: a Complicated System?mentioning
confidence: 99%
“…A central assertion of this paper is that interdisciplinary systems primarily function as complicated systems, unlike multidisciplinary research systems which, as discussed in Dalton et al (2021), may be considered as complex systems. Indeed, as noted by Poli (2013), distinctions between complex and complicated systems are gradually becoming more uncertain (somewhat ironically) because of the increasing literature on complex systems.…”
Section: Interdisciplinary Research: a Complicated System?mentioning
confidence: 99%
See 2 more Smart Citations